The h‐SbxWO3+2x Oxygen Excess Antimony Tungsten Bronze. Issue 8 (9th January 2019) - von Rohr, Fabian O.; Ryser, Alice; Ji, Huiwen; Stolze, Karoline; Tao, Jing; Frick, Jessica J.; Patzke, Greta R.; Cava, Robert J.
Abstract: We describe the previously unreported oxygen excess hexagonal antimony tungsten bronze with composition Sb0.5 W3 O10, in the following denoted as h ‐Sb x WO3+2 x with x =0.167, to demonstrate its analogy to classical Ax WO3 tungsten bronzes. This compound forms in a relatively narrow temperature range between 580 °C< T <620 °C. It was obtained as a dark‐blue polycrystalline powder, and as thin, needle‐shaped, blue single crystals. h ‐Sb x WO3+2 x crystallizes in the hexagonal space group P 6/ mmm with the cell parameters a =7.4369(4) Å and c =3.7800(2) Å. The antimony and excess oxygen occupy the hexagonal channels within the network of corner‐sharing WO6 octahedra. h ‐Sb x WO3+2 x has a resistivity of ρ 300 K ≈1.28 mΩ cm at room temperature, with little if any temperature‐dependence on cooling. DFT calculations on a simplified model for this compound find a metallic‐like electronic structure with the Fermi level falling within rather flat bands, especially around the Γ point. Abstract : Tungsten bronzes are a class of insertion compounds consisting of a network of corner‐sharing [WO6 ] octahedra. There has been a logical deficiency in the structural chemistry of antimony tungsten bronzes, which is now bridged with the here reported discovery of a hexagonal tungsten bronze h ‐Sb x WO3+2 x with x =0.167. This blue, metallic bronze consists of [SbO2 ] + chains along the hexagonal channels.